Audience Reception Analysis of Feminism in Difficulty Being Woman Mata Najwa 2 - Sekar Kedaton, Kirana Ratu; Dewi Swastika, Gabriela Laras (Al-MUNZIR, 2024)
Social media exposure is impossible to avoid in this era and changes in communication behavior for individuals and groups to become more open and active. Based on Report data for 2023, there were 139 million YouTube users in Indonesia as of January 2023, which is estimated to increase to 81.82% of the population in 2026. This bombastic number is considered effective for spreading campaigns for women's rights and feelings through social media, which discusses stereotypes, gender equality, and feminism contained in Wati's 2022 research on Spreading Gender Equality Values Through YouTube. YouTube content that can accommodate it is "The Difficulty of Being a Woman Part 2" on the Najwa Shihab channel. Researchers want to find out how the media audience's reception of Najwa Shihab's content feminism using quasi-qualitative research method with reception analysis approach of the Stuart Hall encoding-decoding model and literature review. Observing and doing FGD with several informants who are included in the four Nightingale audience typologies namely audiences, media target audiences, and audiences with interactive experience. Researchers find that construction and media representation have a big impact on audience reception. The highest reception is on the difficulty being woman motion, meanwhile, the aged standard of woman married, the matters of beautifulness, and non idealistic reason of woman become leader is on negotiating. All informants refused the domestication and pregnancy plan charged to women. The audience as the people addressed is on opposite sides of every motion and the others give the diversity answers in each reading position.